A campus microgrid used as an active learning tool for new generation of electrical power engineers. Issue 4 (October 2022) - Khan, Kaisar R; Haque, Muhammad M; Sachdeva, Dinesh; Morgan, Mitchell BK
We are demonstrating that a campus microgrid can be used as a learning tool to prepare electrical power engineers for the new millennium. A project-based extrapolated active learning method using this microgrid is adopted to train students, the industry standard tools, system, and practices. Digital computer-based automation techniques for microgrid operation make an exciting learning experience for the new generation of students who are daily users of digital technology. The method is intended to prepare them with skills necessary to operate, design and develop the evolving smarter grid. A positive trend in student learning outcome and positive feedback from industry professionals reflects the contribution of this microgrid as a training tool where industry professionals and academia work symbiotically. Evidence shows that students who graduated with this training were employed in the respective area and the supervisor from the industry finds the teaching techniques effective.